The Impact of Healthcare Worker Safety Culture on Outpatient Patient Satisfaction in Public Hospitals - Rahman, Ferry Fadzlul; Darsono, Susilo Nur Aji Cokro; Oktaviani, Lisa Wahidatul; Thipwong, Phanee (Universitas Muhammadiyah Yogyakarta, 2024)
Patient satisfaction and the safety culture of health workers are two important aspects that are interrelated in providing health services. Patient satisfaction measures the extent to which patients are satisfied with the services they receive from health service providers. This study analyzes the impact of safety culture and factors related to outpatient patient satisfaction. Observational research was employed with stratified random sampling, and primary data was collected from a public hospital in Samarinda City. The study included patients who had received outpatient care within the last 3 days, aged 17 years and older, and willing to complete the questionnaire. Inpatients were excluded from the sample criteria. The bivariate test was performed for chi-square, then binary logistic for multivariate. Statistical test results of the variables clarity of information, communication of health workers, physical quality, empathy, and safety culture associated with outpatient satisfaction, multivariate regression showed safety culture (OR 13.44; p 0.006) had a large influence, followed by communication (OR 12.460; p 0.023) and empathy (OR 9.947; p 0.025) on outpatient satisfaction. This research is expected to be a source of information, input, and material for preparing plans and as a basis for the initial stages of periodic evaluation of the quality of health services for patients.